Alteraciones A Nivel Morfológico Generadas Por Analgésico De Uso Comun En Pez Cebra (Danio rerio) (2018)
The Zebrafish is a perfect model in aquatic toxicology and biomedicine, for research and knowledge of the possible adverse effects of different substances, especially synthetic type, like analgesic drugs, which currently are use world wide for pain relief and can be purchased without medical formula, usually it doesn´t need a prescription, in addition, most people are unaware of their side effects in the stages of development and subsequent to these. The objective of this study was to evaluate possible morphological alterations caused by dipyrone (metamizol) in the development of the Zebrafish (Danio rerio) during 15 days after fertilization, in three concentrations of dipyrone (3.57, 7.14 and 10.7 μg / ml). A completely randomized block design with an equal number of replications was performed, with 4 treatments and 4 repetitions per treatment in which 20 eggs were used for each one and were evaluated micro and macroscopically. It was obtained as results that the individuals submitted to the drug presented alterations such as oculocutaneous depigmentation, spinal alterations, pericardial edema, yolk sac edema, abnormal formation in eyes, hemorrhages, reduced gaseous bladder showing an increase in alterations and the development of individuals with hyperdilation. Of the crystalline concentration 3 (10.7 μg / ml) which corresponds to the highest dose.